Preoperative Surgical Fear, Postoperative Pain, and Sleep Quality in Metabolic and Bariatric Surgery Patients: A Descriptive and Correlational Study - Dogan, Sevgi Deniz; Gunes, Dilek; Yurtseven, Seyma; Arslan, Sevban; Gulsen, Muaz; Kirkil, Cuneyt (Springer, 2025)
Background This study aimed to determine the preoperative surgical fear levels, postoperative pain intensity, and sleep quality of metabolic and bariatric surgery patients and to examine the relationship between them. Methods This study was a single-center descriptive and correlational design and was completed with 115 patients. The data of the study were collected by using the Personal Information Form, Surgical Fear Questionnaire, Richards-Campbell Sleep Questionnaire, and Visual Analog Scale. Descriptive statistics, Pearson correlation, and multiple linear regression analysis were used for data analysis. Results In the study, the mean total score of the preoperative Surgical Fear Questionnaire was 24.73 +/- 16.32, and the mean total score of the Richards-Campbell Sleep Questionnaire on the 1st postoperative day was 53.85 +/- 20.53. The mean postoperative pain intensity scores were 7.44 +/- 1.74 at the 1st hour, 5.19 +/- 1.61 at the 12th hour, and 3.24 +/- 1.85 at the 24th hour. In addition, it was determined that surgical fear and postoperative pain significantly predicted sleep quality (p < 0.05). Conclusions It was determined in the study that sleep quality decreased as the level of surgical fear and pain intensity of the patients increased. Considering the relationship between fear of surgery, postoperative pain, and sleep quality, it may be beneficial to develop support and counseling services for patients according to current guidelines.
Keywords: Bariatric surgery; Fear; Nursing; Postoperative pain; Sleep quality